Effects of Lactobacillus rhamnosus probiotic supplementation on gut health in rabbits - Taghreed AL-fakje; Faeha Al-Mashhadane; Asmaa Al-Nuaimy (Medicinski glasnik, 2026)
Aim: The research examined the effects of prolonged oral Lactobacillus rhamnosus intake on rabbit intestinal tissue morphology. Methods: The study included twelve male rabbits aged 10-12 months and weighing 1.5-2.0 kg who received random assignment to two groups of six animals each. The control group received distilled water but the experimental group received L. rhamnosus orally at 0.25 mL/kg/day for 45 days. The research team performed histological and morphometric analysis on duodenal samples to measure villus height and width and crypt depth and villus area and VH/CD ratio and muscularis thickness through ImageJ software. Results: The extended probiotic treatment caused villus disorganization and epithelial necrosis and villus fusion and inflammatory infiltration and submucosal edema. The quantitative analysis showed that all measured parameters including villus height and VH/CD ratio and villus area and muscularis thickness demonstrated significant decreases (p<0.05) when compared to the control group. The results show that absorptive capacity was impaired. Conclusion: The duodenal mucosa developed structural and functional changes because of extended exposure to high L. rhamnosus concentrations which indicates that long-term probiotic use could be harmful. Research needs to determine the correct dosage amounts and duration of treatment for non-rodent species.
Keywords: Lactobacillus rhamnosus; probiotics; Rabbits; histopathology; Gut health; Morphometry.